The Role of Artificial Intelligence in Improving the Quality of Student Learning Process - Yusuf, Nasrullah (GoAcademica Research & Publishing, 2024)
Artificial intelligence (AI) technology has become integral to student learning in the digital era. This article investigates the role of AI in improving the quality of the student learning process, focusing on personalization of learning, adaptive evaluation, and learning data analysis. This research uses a qualitative research approach. The research design adopted is a case study, which allows us to understand the implementation of artificial intelligence in student learning deeply. The research population and sample were 100 students at the Indonesian Technocrat University in Lampung province, Indonesia. The research results show that implementing AI in education has great potential to increase learning effectiveness, inclusiveness and efficiency. This confirms that adopting AI technology can significantly strengthen students' academic performance and prepare them to face future challenges.